Biomechanical analysis of two long jump take-off techniques - Bridgett, L. A.; Linthorne, N. P. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
A technique intervention strategy was used whereby the run-up velocities of two long jumpers were systematically varied. The take-off parameters that define the athlete's take-off technique showed reproducible changes in response to changes in run-up speed. The two athletes in the study used slightly different take-off techniques to achieve their performances.